PEMANFAATAN AUGMENTED REALITY UNTUK PENGENALAN HARDWARE KOMPUTER PADA SEKOLAH DASAR BERBASIS ANDROID - Redaksi Tim Jurnal (PETIR, 2017)
Augmented reality is a technology that is currently being developed a lot in the field of games or entertainment. Unfortunately this augmented reality is still a little to work with in the field of education, in the field of education are currently still widely dominated the book that impressed monotonous and not liked by the children of elementary school age. Whereas such material to support the material about the devices the computer taught to elementary school students learning the media needed a more interactive and imaginative. Therefore researchers initiative to design and make the application of augmented reality hardware as a means of learning interactive and interesting and can help deliver material about the computers that will be packaged in an android-based applications. This application will display a different augmented reality applications that have been there before because using media android devices and using different marker i.e. color images of objects that are displayed. This application is created by using software Unity 3D that have plus asset Vuforia SDK.